2017
DOI: 10.1016/j.amsu.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

A case report of pneumo-retro-peritoneum: An unusual presentation of ischio-rectal abscess

Abstract: IntroductionAno-rectal abscesses are common. They however usually do not present with abdominal symptoms. CT although useful is not routinely carried out. Finding of Pneumo-retro-peritoneum with ischio-rectal abscess is rare.Case presentationWe present the case of a diabetic gentleman who presented with abdominal pain and distension and was found to have ischio-rectal abscess on perianal examination. Although initially suspected to have acute abdomen due to perforated viscus, CT scan revealed pneumo-retro-peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In abscesses with massive pre- or retroperitoneal extension, access to the peritoneal cavity must be avoided due to the high risk of contamination and secondary peritonitis. Optimal treatments have been proposed by different authors, including abdominal stab-like incisions [ 7 ] or extraperitoneal drainage with lower midline abdominal incision with excellent outcomes [ 8 , 9 ]. The wound can be closed primarily with drains or with vacuum assistance devices [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In abscesses with massive pre- or retroperitoneal extension, access to the peritoneal cavity must be avoided due to the high risk of contamination and secondary peritonitis. Optimal treatments have been proposed by different authors, including abdominal stab-like incisions [ 7 ] or extraperitoneal drainage with lower midline abdominal incision with excellent outcomes [ 8 , 9 ]. The wound can be closed primarily with drains or with vacuum assistance devices [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite our literature review one case report of retroperitoneal air due to an ischiorectal abscess was found. 4 Another case report of hip pain and inability to ambulate due to ischiorectal abscess. 5 Given supralevator space proximity to the hip, it is speculated that this is the reason for hip pain and gas presenting in or near the hip joint.…”
Section: Discussionmentioning
confidence: 99%